2022
DOI: 10.1371/journal.pone.0268892
|View full text |Cite
|
Sign up to set email alerts
|

Mapping HIV prevalence in Nigeria using small area estimates to develop a targeted HIV intervention strategy

Abstract: Objective Although geographically specific data can help target HIV prevention and treatment strategies, Nigeria relies on national- and state-level estimates for policymaking and intervention planning. We calculated sub-state estimates along the HIV continuum of care in Nigeria. Design Using data from the Nigeria HIV/AIDS Indicator and Impact Survey (NAIIS) (July–December 2018), we conducted a geospatial analysis estimating three key programmatic indicators: prevalence of HIV infection among adults (aged 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The relatively lower prevalence of cervical epithelial abnormalities in our study may reflect the population of women enrolled as the study site is an HIV treatment centre where almost all clinic attendees are already on ART. Furthermore, the prevalence of cervical cytological abnormalities closely reflects the burden of HIV reported in the geographical settings of these respective studies [21,22]. The higher prevalence rates of cervical epithelial abnormalities in this study and others [16,19,23] compared to the figures reported in the general women population (3.5-4.1%) [24][25][26] comprising predominantly HIV seronegative women are not unexpected as HIV-infected women are more likely to have persistent oncogenic HPV infections which predispose them to cervical precancers and cancer [2,4].…”
Section: Discussionmentioning
confidence: 98%
“…The relatively lower prevalence of cervical epithelial abnormalities in our study may reflect the population of women enrolled as the study site is an HIV treatment centre where almost all clinic attendees are already on ART. Furthermore, the prevalence of cervical cytological abnormalities closely reflects the burden of HIV reported in the geographical settings of these respective studies [21,22]. The higher prevalence rates of cervical epithelial abnormalities in this study and others [16,19,23] compared to the figures reported in the general women population (3.5-4.1%) [24][25][26] comprising predominantly HIV seronegative women are not unexpected as HIV-infected women are more likely to have persistent oncogenic HPV infections which predispose them to cervical precancers and cancer [2,4].…”
Section: Discussionmentioning
confidence: 98%
“…Internationally, previous research on small-area variations in the prevalence of HIV have used small-area estimation techniques. Most of these studies were conducted in African countries [8][9][10][11]. One study from the USA estimated the number of people with HIV in 677 counties where HIV case numbers were not previously available [12].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] There is evidence of geographic variation in coverage and viral suppression, 17 18 including Nigeria, with local government variation in ART coverage and viral suppression. 19 Nigeria is the most populous country in Africa, 20 has an HIV prevalence of 1.4%, 21 with a state-level prevalence of 0.3%-4.8%, and more prevalent in the rural areas than the urban area. 22 Like many other Sub-Saharan African countries, many people in Nigeria reside in rural areas, with up to 47.3% of Nigerians living in rural areas in 2021.…”
Section: Open Accessmentioning
confidence: 99%